2022
DOI: 10.1515/jpem-2022-0474
|View full text |Cite
|
Sign up to set email alerts
|

Comparative characteristics of developing morphofunctional features of schoolchildren from different climatic and geographical regions

Abstract: Objectives Adaptation processes in body of schoolchildren, along with study load and social factors, are determined by influence of climatic and geographical factors of residence region. This research has been undertaken to study the morphofunctional characteristics of schoolchildren at the age of 7–17 years. Methods The research involved 880 schoolchildren of both sexes in age from 7 to 17 years, studying in secondary school… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…According to the Cognitive Theory of Multimedia Learning [77], instructional materials with high-quality content and appropriate multimedia elements can enhance learners' cognitive processing and information retention. Engaging and interactive multimedia elements, such as videos, graphics, animations, and simulations, can facilitate the understanding of complex concepts, promote active learning, and increase learners' motivation [78,79]. Research has consistently shown that learners perceive highquality content as more relevant, credible, and valuable, leading to higher levels of engagement and the intention to participate in e-learning activities.…”
Section: -Findings and Discussionmentioning
confidence: 99%
“…According to the Cognitive Theory of Multimedia Learning [77], instructional materials with high-quality content and appropriate multimedia elements can enhance learners' cognitive processing and information retention. Engaging and interactive multimedia elements, such as videos, graphics, animations, and simulations, can facilitate the understanding of complex concepts, promote active learning, and increase learners' motivation [78,79]. Research has consistently shown that learners perceive highquality content as more relevant, credible, and valuable, leading to higher levels of engagement and the intention to participate in e-learning activities.…”
Section: -Findings and Discussionmentioning
confidence: 99%
“…Logical reasoning is the cognitive skill that involves the application of principles of logic, deduction, and inference to draw conclusions, make connections, and identify patterns or relationships between different pieces of information (Stanovich, 2010;Mukataeva et al, 2022). It encompasses the ability to recognize and apply logical rules, identify inconsistencies, analyze cause-effect relationships, and think in a systematic and structured manner.…”
Section: Logical Reasoningmentioning
confidence: 99%
“…The existing body of studies pertaining to employee-related factors remains rather limited despite those factors recognized as a strategic lever for the organization to have a competitive advantage over other organizations (Mukataeva et al, 2023;Dwijendra et al, 2021).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%